Design and application of oral colon administration system. (1st January 2019) - Cheng, Hao; Huang, Shiyu; Huang, Gangliang
Abstract: Oral colon administration system has become a new method to treat intestinal diseases. The implementation of colon drug delivery system is restricted by many aspects, including physical and chemical properties, drug delivery mode, gastrointestinal physiological factors, and so on. Delivery methods to overcome these challenges revolve around the mechanisms of drug delivery, including the use of rational dosage forms to avoid the complex pH environment, and the prevention of drug release and absorption in the upper digestive tract.